2008
DOI: 10.2478/v10018-009-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Assessment of Digital Elevation Models Using GPS

Abstract: ABSTRACT.A Digital Elevation Model (DEM) is a digital representation of ground surface topography or terrain with different accuracies for different application fields. DEM have been applied to a wide range of civil engineering and military planning tasks. DEM is obtained using a number of techniques such as photogrammetry, digitizing, laser scanning, radar interferometry, classical survey and GPS techniques. This paper presents an assessment study of DEM using GPS (Stop&Go) and kinematic techniques comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…For instance, [39] stated that the use of total station provided accuracy with an error of approximately 1 cm in horizontal position and about 2 cm in vertical position (elevation). The studies [40,41] used total station ground-truthed data to assess the accuracy of LiDAR, and [42] used it to assess the accuracy of GPS.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, [39] stated that the use of total station provided accuracy with an error of approximately 1 cm in horizontal position and about 2 cm in vertical position (elevation). The studies [40,41] used total station ground-truthed data to assess the accuracy of LiDAR, and [42] used it to assess the accuracy of GPS.…”
Section: Discussionmentioning
confidence: 99%
“…Walker and Willgoose [45] assessed the accuracy of their Total Station data using error propagation theory and found that uncertainty in position is ∼1 cm and uncertainty in elevation is ∼2 cm. Shrestha et al [46] used traditional surveying techniques to acquire profiles to assess the accuracy of LiDAR; Töyrä et al [47] used Total Station elevation data to assess LiDAR; and Farah et al [48] used Total Station data to assess the accuracy of DEMs derived from GPS. In a number of these studies the Root Mean Squared Error (RMSE) for each dimension and the total RMSE have been used as accuracy metrics.…”
Section: Georeferenced Point Clouds and Reference Datamentioning
confidence: 99%
“…The elevations were collected using two GPS instruments (Topcon Hiper GGD; model Lite Plus) with dual-frequency receivers in a real-time kinematic (RTK) configuration. The application of GPS RTK has proven effective as a fast, precise method to collect reference data for studies that investigate terrain elevation (FARAH et al, 2008;KIZIL & TISOR, 2011). One GPS unit (termed Base) was installed near the center of the study area, and the other (termed Rover) was carried throughout the study area to a maximum distance of 2 km from the Base.…”
Section: Methodsmentioning
confidence: 99%